Hubungan Frekuensi Hemodialisis dengan Kualitas Hidup pada Pasien Gagal Ginjal Kronik - Moh. Aufa Rikhil Angfakh; Moh. Wildan; Hendra Dwi Cahyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2024)
Background: Chronic renal failure is a condition that shows abnormalities in kidney structure or function and affects health conditions. Hemodialysis is the main therapy for chronic renal failure patients. Hemodialysis is performed with a frequency of 8-12 times per month for 3-4 hours per hemodialysis session. Patients who undergo hemodialysis will affect their quality of life. Purpose: The purpose of this study was to determine the relationship between hemodialysis frequency and quality of life in patients with chronic renal failure undergoing hemodialysis. Methods: The research design used correlational analysis with a Cross-Sectional approach. Non-probability sampling technique with consecutive sampling approach totaling 40 samples. The research instrument used the World Health Organization Quality of Life-Bref (WHOQol-BREF) questionnaire. Bivariate test using Fisher's Exact Test. Results: The results of the Fisher's Exact Test bivariate test obtained a value of p = 0.000 (p <0.05). The conclusion of this study shows a correlation between the frequency of hemodialysis and quality of life in patients with chronic renal failure. Implication: Determining the frequency of hemodialysis needs to consider the results of urea and creatinine examinations both before and after hemodialysis as well as things that need to be considered and how to handle them. Through the application of appropriate management, it can improve the quality of life of patients with chronic renal failure.